Staff management in library and information work - Jordan, Peter, 1936-; Lloyd, Caroline, 1968- (Abingdon, Oxon : Routledge, 2017)
"This standard text has been fully revised and updated for its fourth edition to reflect continuing technological changes, as well as issues such as social inclusion, lifelong learning and European employment legislation. Chapter 1 on the working environment has been completely rewritten. The present environment brings problems of staff motivation, de-professionalization and the loss of control: Chapter 2 reminds readers of basic motivation theories, now presented in a more logical sequence, and how to deal with such problems. Chapter 3 on workforce planning has been retitled Human Resource Planning and revised to take into account the modes of staffing appropriate for today's turbulent environment. Effective human resource planning requires excellent selection and recruitment procedures: best practice and developments in this area are explored in Chapters 4, Job Descriptions and Person Specifications, and 5, Recruitment and Selection of Staff. In Chapter 6 on staff appraisal more attention has been given to multi-rating approaches, such as 360A whereby different aspects of work can be assessed by different groups of people, and to appraisal of junior by senior staff. The last decade has seen increased emphasis on training and development to deliver high quality services in a climate of constant change. Chapter 7 has therefore been reordered and expanded in order to reflect new approaches and changes in this area. In Chapter 8, Staff Supervision and Interpersonal Skills, recent emphasis on leadership and counselling skills are reflected, as is the growing need to do more with less through enhanced time management and stress management techniques. With this new edition, this core guide brings professionals involved in managing library and information staff up to date with how to cope with the most pressing problems and challenges in today's fast-changing environment."--Provided by publisher.
chapter 1 The working environment -- chapter 2 Motivation and job satisfaction -- chapter 3 Human resource planning -- chapter 4 Job descriptions and person specifications -- chapter 5 Recruitment and selection of staff -- chapter 6 Staff appraisal -- chapter 7 Staff training and development -- chapter 8 Staff supervision and interpersonal skills training.
First published 2002 by Ashgate Publishing.
Includes bibliographical references (pages 289-304).
Keywords: Library personnel management -- Great Britain; Work environment -- United Kingdom; Information services -- Great Britain -- Personnel management